Maize: a survival strategy for rural families in Texcala Morelos, Mexico - Román-Montes-de-Oca, Erika (2019)
Maize (Zea mays L.) is important in the lives of rural families. Being a staple, it has been fundamental in the life strategies of family units for years. Consequently, the impact of maize was analyzed as a contribution to the survival strategies of family units. The study was conducted in the community of Texcala, Yecapixtla Morelos, Mexico. Using an ethnographic method, 33 semi structured interviews were conducted. As a result, 100% of the interviewees was found to have an excess of corn, which is priced higher than normal maize, and 70% combine corn farming with other jobs as a strategy to promote reproduction of the family unit